Upper arm versus forearm transcutaneous oximetry during upper limb abduction in patients with suspected thoracic outlet syndrome - Hersant, Jeanne; Lecoq, Simon; Ramondou, Pierre; Feuilloy, Mathieu; Abraham, Pierre; Henni, Samir (Frontiers in Physiology, 2022)
Context: thoracic outlet syndrome (TOS) is common among athletes and should be considered as being of arterial origin only if patients have “clinical symptoms due to documented symptomatic ischemia”. We previously reported that upper limb ischemia can be documented with DROPm (minimal value of limb changes minus chest changes) from transcutaneous oximetry (TcpO2) in TOS. Purpose: We aimed to test the hypothesised that forearm (F-) DROPm would better detect symptoms associated with arterial compression during abduction than upper arm (U-) DROPm, and that the thresholds would differ. Methods: We studied 175 patients (retrospective analysis of a cross-sectional acquired database) with simultaneous F-TcpO2 and U-TcpO2 recordings on both upper limbs, and considered tests to be positive (CS+) when upper limb symptoms were associated with ipsilateral arterial compression on either ultrasound or angiography. We determined the threshold and diagnostic performance with a receiver operating characteristic (ROC) curve analysis and calculation of the area under the ROC curve (AUROC) for absolute resting TcpO2 and DROPm values to detect CS+. For all tests, a two-tailed p<0.05 was considered indicative of statistical significance. Results: In the 350 upper-limbs, while resting U-TcpO2 and resting F-TcpO2 were not predictive of CS+ results, the AUROCs were 0.68 ± 0.03 vs. 0.69 ± 0.03 (both p<0.01), with the thresholds being 7.5 vs. 14.5 mmHg for the detection of CS+ results for U-DROPm vs. F-DROPm respectively. Conclusion: in patients with suspected TOS, TcpO2 can be used for detecting upper limb arterial compression and/or symptoms during arm abduction, provided that different thresholds are used for U-DROPm and F-DROPm. Registration: ClinicalTrials.gov: NCT04376177